2008
DOI: 10.1002/cne.21852
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of glial glutamate transporters after dopamine denervation in the striatum of 6‐hydroxydopamine‐lesioned rats

Abstract: Overactivity of glutamatergic neurotransmission in the basal ganglia is known to be closely related to the onset and pathogenesis of Parkinson's disease. Glutamate homeostasis around glutamatergic synapses is tightly regulated by two groups of glutamate transporters: glial glutamate transporters GLT1 (EAAT2) and GLAST (EAAT1), and neuronal glutamate transporter EAAC1. In order to investigate the changes of glutamate transporters after the onset of Parkinson's disease, unilateral 6-hydroxydopamine-lesioned rat,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 79 publications
5
69
0
3
Order By: Relevance
“…A similar upregulation of GFAP has been shown in 6-OHDA-or MPTP-lesion models in which the neurotoxins are injected directly into the striatum (Chadi and Gomide 2004;Gomide et al 2005;Henning et al 2008;Yoo et al 2005), the median forebrain bundle (Henning et al 2008;Stromberg et al 1986), or the substantia nigra (Chung et al 2008;Sheng et al 1993). Similar to our findings, the activation of astrocytes in these studies is not restricted to the direct sites of 6-OHDA or MPTP injection but comprise various brain regions (Chadi and Gomide 2004;Gomide et al 2005) that represent target areas of dopaminergic projections.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A similar upregulation of GFAP has been shown in 6-OHDA-or MPTP-lesion models in which the neurotoxins are injected directly into the striatum (Chadi and Gomide 2004;Gomide et al 2005;Henning et al 2008;Yoo et al 2005), the median forebrain bundle (Henning et al 2008;Stromberg et al 1986), or the substantia nigra (Chung et al 2008;Sheng et al 1993). Similar to our findings, the activation of astrocytes in these studies is not restricted to the direct sites of 6-OHDA or MPTP injection but comprise various brain regions (Chadi and Gomide 2004;Gomide et al 2005) that represent target areas of dopaminergic projections.…”
Section: Discussionmentioning
confidence: 78%
“…The injection of the neurotoxin 6-OHDA into the nigrostriatal system can be used to study the effect of dopaminergic depletion not only on neurons or neuronal precursors (Aponso et al 2008;Chung et al 2008;Hoglinger et al 2004;Hu et al 1990;Rodriguez et al 2001), but also on astrocytes (Gordon et al 1997;Henning et al 2008;Sheng et al 1993;Stromberg et al 1986;Yoo et al 2005). We have investigated the effect of 6-OHDA on astrocytes in the striatum and cortex in the adult rat brain, in a model in which the neurotoxin is not injected into the nigro-striatal system but into the lateral ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…There is the possibility that the increased extracellular levels of glutamate associated with loss of DA could result from downregulation of striatal GLT-1. Whereas some groups have reported downregulation of GLT-1 following dopaminergic lesioning (Holmer et al, 2005; Chung et al, 2008), others have observed an upregulation of striatal GLT-1 (Massie et al, 2010). We and others did not detect changes in striatal GLT-1 expression (Lievens et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies demonstrated that EAAT2 expression is involved in PD. Decreased EAAT2 expression has been reported in animal models of PD, including the 6-hydroxydopaminelesioned PD model and the acute 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine treated mouse model [145,146]. Recently, growing evidence shows ceftriaxone has beneficial effects in PD animal model, including the prevention of motor dysfunction, neuronal death, and PD related memory deficits [147][148][149][150][151][152].…”
Section: Parkinson's Diseasementioning
confidence: 99%